WORK-LIFE BALANCE, JOB SATISFACTION, AND EMPLOYEE'S ORGANIZATIONAL COMMITMENT IN CONSTRUCTION COMPANIES - Nugraemi, Ulvita; Faslah, Roni; Dalimunthe, Sholatia (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2023)
This study aims to determine how much influence work-life balance and job satisfaction have on organizational commitment in PT. Karya Adi Kencana Kebumen. The research method used is a survey method using a 5-point Likert Scale. The affordable population in this study amounted to 155 employees with a sample size 112 employees. The sampling technique used purposive sampling technique. The data analysis technique used is multiple regression to answer the research hypothesis data processing using the SPSS version 26.0 program. Data analysis techniques used (1) analysis requirement test consisting of normality and linearity test (2) classical assumption test and heteroscedasticity test (3) multiple linear regression test (4) hypothesis testing consisting of F test and t-test (5) coefficient of determination analysis. The results showed that there was a simultaneous influence of work-life balance and job satisfaction on organizational commitment by 42,7%.